Microwave-Assisted Cyclization of Unprotected Dipeptides in Water to 2,5-Piperazinediones and Self-Assembly Study of Products and Reagents - Kurbasic, Marina; Semeraro, Sabrina; Garcia, Ana M.; Kralj, Slavko; Parisi, Evelina; Deganutti, Caterina; De Zorzi, Rita; Marchesan, Silvia (Synthesis, 2019)
Dipeptides and their cyclized 2,5-piperazinedione (or diketopiperazine, DKP) derivatives are attractive building blocks for supramolecular hydrogels. The Phe-Phe, (p-nitro)-Phe-Phe, and Phe-Val dipeptides and their corresponding DKPs are studied for self-assembly in water. The DKPs were obtained in high yields by microwave-assisted cyclization of the dipeptides in water, demonstrating that use of their methyl ester derivatives as reported in the literature is not necessary for successful cyclization. Single-crystal XRD structures are reported for two DKPs as well as stable hydrogels at neutral pH.
Keywords: dipeptide; diketopiperazine; self-assembly; hydrogels; amyloid; microwaves; 2,5-piperazinedione